Hubungan Kadar Timbal dalam Darah dengan Jumlah Eritrosit Pada Siswa Sekolah Dasar (Studi di SD Negeri Grinting 01 Kecamatan Bulakamba Kabupaten Brebes Jawa Tengah) - Maskinah, Eni; Suhartono, Suhartono; Setiani, Onny (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2016)
Title: The Association Between Blood Lead Levels and Eryhrocyte Counts in Elementary School Students.Background: Lead is a heavy metal that can cause both acute and chronic toxicity to human. Infant and children are usually more sensitive to lead toxicity than adults. The data of CDC (Centre for Desease Control and Prevention) showed that 49% of lead poisoning cases were happened to children with the age of under six year. Lead is known to affect the hematologic system by interfering with heme synthesis and caused anaemia. The aim of this research was to identify the association between blood lead level (BLL) and erythrocyte counts.Method: This research was an observational research using the analytical approach and cross sectional design with 52 students participated in purposive sampling. Blood level as the independent variable and the dependent variable was erythrocyte counts.Results: The research results showed that the mean of BLL was 31,52 µg/dl, the minimum value is 11,6 µg/dl and the maximum value is 48,89 µg/dl. The mean of erythrociyte count was 4,72x 1012/L. Chi Square Test showed that the value of p >0,05, (PR=0,84, 95% CI=0,27-2,63) meaning that there was no association between blood lead level and erythrocyte counts.Conclusion: The children have been exposed to lead according to standards set by CDC, which 5 µg/dl average 31,52 µg/dl. There was no association between blood lead level and erythrocyte counts (p>0.05).